1991
DOI: 10.1001/archsurg.1991.01410300029003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Venous Insufficiency in Patients With Varicose Veins

Abstract: The nature and distribution of venous disease surrounding the development of varicose veins and its treatment is controversial. Using duplex ultrasonography, we evaluated 54 lower extremities in 32 patients with varicose veins who were symptomatic and had obvious varicose veins by clinical examination. Twenty-eight percent had greater saphenous trunk incompetence, 2% had lesser saphenous trunk incompetence, and 96% had branch disease. Deep valvular incompetence was seen in 41%, saphenofemoral junction incompet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 8 publications
0
21
0
3
Order By: Relevance
“…When duplex ultrasound is used on a patient population that also includes smaller veins, it has been shown that segmental or regional reflux frequently occurred in the long saphenous vein, at any level, without evidence of refluxthrough the sapheno-femoral junction or reflux from other 'transfascial escape' sources [5][6][7]. These findings shifted attention from primary valvular incompetence to primary vein wall dilatation as an alternative, more acceptable aetiological explanation [8], Focusing on the sapheno-femoral junction, van Bernmelen and Sumner investigated reflux patterns with duplex ultrasound in patients with varicose veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…When duplex ultrasound is used on a patient population that also includes smaller veins, it has been shown that segmental or regional reflux frequently occurred in the long saphenous vein, at any level, without evidence of refluxthrough the sapheno-femoral junction or reflux from other 'transfascial escape' sources [5][6][7]. These findings shifted attention from primary valvular incompetence to primary vein wall dilatation as an alternative, more acceptable aetiological explanation [8], Focusing on the sapheno-femoral junction, van Bernmelen and Sumner investigated reflux patterns with duplex ultrasound in patients with varicose veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been well established that varicosities involve the tributaries and the accessory veins. [5][6][7] Varicosities in the main trunk of the great and small saphenous veins (GSV and SSV) have been reported, [5][6][7][8][9] but not the exact distribution and extent throughout the saphenous venous system. Additionally, reflux of the saphenous trunks has been implicated in the development of varicose veins, [10][11][12][13] yet this correlation in conjunction with the distribution of the varicosities remains to be elucidated.…”
mentioning
confidence: 99%
“…[1][2][3] The reported annual incidence of new cases of varicose veins is 2.6% in women and 1.9% in men, with associated costs to the community in terms of lost working hours, hospitalization, and management. 4,5 Two theories have been proposed to describe the pathogenesis of varicose veins: the valvular theory and primary weakness of the venous wall.…”
mentioning
confidence: 99%
“…[10][11][12][13] The influence of increased levels of female sex hormones, especially during pregnancy, on venous disorders of the legs has been noted by many investigators. [1][2][3][4][5][14][15][16][17][18][19][20] In addition, estrogen and progesterone receptors were found in sections of venous walls, suggesting an involvement of sex hormones in the pathogenesis of varicose veins by a mechanism that has yet to be identified. [21][22][23][24] To elucidate any effect of sex hormones on veins containing these receptors, we performed this in vivo study during the menstrual cycle in young women.…”
mentioning
confidence: 99%